Task-Dependent Postural Control Throughout The Lifespan - Haddad, Jeffrey M. (2013)
Routine activities performed while standing and walking require the ability to appropriately and continuously modulate postural movements as a function of a concurrent task. Changes in task-dependent postural control contribute to the emergence, maturation, and decline of complex motor skills and stability throughout the lifespan.